Thermal analysis of vehicle engine - Mohd Fauzie, Ramli (2008)
This thesis deals with thermal analysis in internal combustion engine. The objective of this thesis is to develop finite element model of combustion chamber for thermal analysis, to obtain the temperature distribution in combustion chamber and its surrounding component, and to determine localized temperature region in the engine. Finite element method (FEM) was employed to develop computational model to analyze the temperature distribution in the engine components and to identify the critical temperature in the components. Computational domain consists of combustion chamber as major part and its surrounding components such as valves, and exhaust port and water jacket. Two types of combustion process were modelled: Spark ignition engine and compression ignition engine. 2-dimensional (2D) simplified models was developed using general-purpose FE code, ALGOR. The element type was 2D element. Material properties were taken from ALGOR library. Heat convection due to the presence of water was defined by convection coefficient. Thermal load due to combustion was defined to all nodes of combustion chamber. The finite element models were analyzed using the thermal transient heat transfer analysis. The finite element model was validated by comparing the maximum temperature at the piston surface with the published result. The results were found to be agreeable. The computed results indicate that the exhaust part may reach the highest maximum temperature in the engine after combustion occurred. In SI engine, the critical component in thermal effect is the cylinder head and for the CI engine is at the piston bowl. Furthermore, the material used to construct the engine part strongly influences the temperature distribution in the engine. Therefore, the performance of the engine at very high temperature can be improved by changing material and design of component. From the analysis, the capability of diesel engine to resist thermal contact is higher compare to gasoline engine because of using higher thermal resistance material with suitable shape and geometry design.